STICHOSIPHON-MANGLE SP-NOVA, A NEW CYANOPHYTE FROM MANGROVE ENVIRONMENTS - Branco, LHZ; Silva, SMF; Santanna, C. L. (E Schweizerbart'sche Verlags, 1994)
A new species of epiphytic Cyanophyceae, Stichosiphon mangle, is proposed. It differs from S. sansibaricus in the planes of cell division during exocyte formation and the habitat. Stichosiphon mangle was found on Inhaca Island, Mozambique (26-degrees-03'S, 32-degrees-57'E), growing up on Gelidium sp. and Murrayella sp. and on Cardoso Island, Brazil (25-degrees-10'S, 48-degrees-W, on Bostrychia spp.
Keywords: STICHOSIPHON-MANGLE SP-NOV; CYANOPHYCEAE, MANGROVE, BRAZIL, MOZAMBIQUE